The Persuasion Strategies Used in Media Discourse: Jordanian Defense Orders and Press Conferences Held during the Covid-19 Pandemic - Alserhan, Faisal Ahmad (Dirasat: Human and Social Sciences, 2024)
Objective: This study aimed to investigate the persuasion strategies used in the Jordanian defense orders 16 through 31 and press conferences held during the Covid-19 pandemic. Method: Within Critical Discourse Analysis, the study adopts van Dijk's (2000) model as a theoretical framework. It is a practical method for analyzing discourse, where many strategies were demonstrated, mainly metaphor, actor description, burden, euphemism, modality, repetition, and numbers. Results: The findings revealed that defense orders did not use persuasion strategies much but used very direct intimidating discourse because they are statements issued by the government to the people living in Jordan and they must abide by them without the need to implement persuasion strategies. Conversely, press conferences extensively used persuasive strategies to convince people to adhere to the rules, so they help the government combat the pandemic. The mostly used persuasion strategies are repetition, followed by numbers, and then, metaphors and burden. Conclusions: The study concludes that both the government and the majority of the public worked hand in hand to face the pandemic and keep Jordan safe, but in the beginning, it was a difficult situation for both. It is recommended that official government speakers who usually deliver public speeches shall be trained on how to persuade the public and what strategies they need to use.